The Effectiveness of Mind Map as a Teaching Tool for Medical Students - Suriya, Sidayu; Suwantarat, Nuntra; Vanicharoenchai, Vorawan; Iramaneerat, Cherdsak (Asian Medical Journal and Alternative Medicine, 2022)
Objective: The mind map has been proven for improving learning effectiveness. We hypothesized that the mind map is helpful to enhance learning outcomes by increasing knowledge retention and student perception for 3rd year medical students at the Faculty of Medicine, Naresuan University. Methods: A randomized controlled trial study was conducted by comparing the academic performance (MCQs scores for pre-test, immediate post-test, and delayed post-test) and the improvement in academic performance in each group by using the paired t test and the students’ perception survey (Assessing Student Perspective of Engagement in Class Tool, ASPECT) after attending the class of “osteoporosis” lecture with mind map (intervention group) and lecture with slides (control group). Results: Thirty-two students were enrolled, but only 28 students completed all the tests (n = 14 in each group). Both groups had no differences in age, gender, academic performance, or pre-test scores (mean of 3.36 in the intervention group vs. 3.34 in the control group). Both groups had similar increases in the immediate post-test score mean of 7.36 (intervention group) and 6.51 (control group) and the delayed post-test score mean of 6.07 (intervention group) and 6.00 (control group). Both groups’ post-test and delayed post-test scores increased significantly (P < .0001). There was a trend of higher ASPECT scores in the intervention group in the item “The instructor’s enthusiasm and class interesting” (P = .07). Conclusions: The lecture with a mind map was effective in improving the academic performance of medical students by increasing students’ engagement and attention during the class.